2016
DOI: 10.7554/elife.11614
|View full text |Cite|
|
Sign up to set email alerts
|

Genetic dissection of Down syndrome-associated congenital heart defects using a new mouse mapping panel

Abstract: Down syndrome (DS), caused by trisomy of human chromosome 21 (Hsa21), is the most common cause of congenital heart defects (CHD), yet the genetic and mechanistic causes of these defects remain unknown. To identify dosage-sensitive genes that cause DS phenotypes, including CHD, we used chromosome engineering to generate a mapping panel of 7 mouse strains with partial trisomies of regions of mouse chromosome 16 orthologous to Hsa21. Using high-resolution episcopic microscopy and three-dimensional modeling we sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
147
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(154 citation statements)
references
References 55 publications
6
147
0
1
Order By: Relevance
“…This has led to the development of the most complete ‘triple trisomic mouse’ which develops Down syndrome‐related neurological impairments . The Dp1Tyb and Dp16 contain the largest duplication of Mmu16, carrying an extra copy of 148 genes which is the entire region of Mmu16 that is orthologous to Hsa21 and does not perturb genes on any other chromosomes . Whilst the triple trisomic mouse is incredibly labour intensive and costly to produce, assessing each individual trisomic mouse is providing further insight into the contribution of gene imbalance to Down syndrome phenotype.…”
Section: Mouse Models Of Down Syndromementioning
confidence: 99%
“…This has led to the development of the most complete ‘triple trisomic mouse’ which develops Down syndrome‐related neurological impairments . The Dp1Tyb and Dp16 contain the largest duplication of Mmu16, carrying an extra copy of 148 genes which is the entire region of Mmu16 that is orthologous to Hsa21 and does not perturb genes on any other chromosomes . Whilst the triple trisomic mouse is incredibly labour intensive and costly to produce, assessing each individual trisomic mouse is providing further insight into the contribution of gene imbalance to Down syndrome phenotype.…”
Section: Mouse Models Of Down Syndromementioning
confidence: 99%
“…The most recent data suggest that many Hsa21 (i.e. dosage-sensitive) genes are required for development of CHD, but that no single gene may be required [131,132].…”
Section: Congenital Heart Defects and Cardiovascular Disease In Down mentioning
confidence: 99%
“…Cardiac malformations have also been observed in Dp(16)1Yey E18.5 embryos, including VSD, ASD, cleft mitral valves, severe coarctation of the aorta, double outlet right ventricle (DORV) and tetralogy of Fallot (TOF) [5]. In a recent study, Lana-Elola et al (2016) generated seven different mouse strains that carry different segmental trisomies of Hsa21 orthologous genes (including the Dp(16)Tyb1 mouse model equivalent to the Dp(16)1Yey model) to identify candidate genes or regions that are responsible for heart defects in DS [30]. They examined embryos at E14.5 using high-resolution episcopic microscopy (HREM) and found that 61.5% of the Dp1Tyb (carrying a duplication of 148 genes between Lipi - Zbtb21 similar to the Dp16 mice) and 44% in the Dp3Tyb (carrying a duplication of 40 genes between Mir802 - Zbtb21 ) present with heart defects, including AVSD, VSD and ASD.…”
Section: Discussionmentioning
confidence: 99%
“…They examined embryos at E14.5 using high-resolution episcopic microscopy (HREM) and found that 61.5% of the Dp1Tyb (carrying a duplication of 148 genes between Lipi - Zbtb21 similar to the Dp16 mice) and 44% in the Dp3Tyb (carrying a duplication of 40 genes between Mir802 - Zbtb21 ) present with heart defects, including AVSD, VSD and ASD. These authors, however, also identified a high incidence of heart defects in WT littermates from these two new strains (27% and 12% of WT in the Dp1Tyb and Dp3Tyb strains, respectively) [30]. …”
Section: Discussionmentioning
confidence: 99%